The effect of biceps tenotomy on clinical results in patients with rotator cuff rupture (Annals of Medical Research, 2021)
Aim: This study aims to evaluate the effect of tenotomy on clinical and radiological outcomes in the treatment of biceps long head tendon pathologies associated with rotator cuff tears.Material and Methods: The study was conducted with 66 patients who met the inclusion criteria and were available (Group 1: Tenotomy, n = 40; Group 2: Non-tenotomy, n = 26). Clinical evaluation of the patients was performed with Modified Constant-Murley Scoring, radiological evaluation with ultrasonography, functional evaluation with dynamometer and visual evaluation with the detection of Popeye Sign finding. Results: The mean age of the patients in group 1 was 58.17 ± 7.95, the follow-up period was 28.87 months, the mean age of the patients in group 2 was 60.61 ± 4.66, and the follow-up period was 35.28 months; there was no statistically significant difference between two groups (p> 0.05). The mean score of the patients in group 1 was 89.83 ± 7.87, whereas the mean score of the patients in group 2 was 86.19 ± 7.07 (p> 0.05). In the ultrasonographic examination, the tendon cut in 24 (60%) of the 40 patients who underwent tenotomy was seen in the bicipital groove, but not in the groove in 16 (40%) patients, but only 3 of these patients had “Popeye Sign” findings.Conclusion: Tenotomy for the treatment of biceps tendon pathologies associated with rotator cuff tear may be an effective treatment method in terms of cost, pain relief and postoperative rehabilitation in the appropriate patient group.Keywords: Rotator cuff, long head of biceps, tenotomy, popeye sign.
Keywords: Rotator cuff, long head of biceps, tenotomy, popeye sign.